Analysis of flow behaviour of iron and steel using power law models. Issue 8 (24th May 2017) - Gupta, C.; Kumawat, B.
Abstract : The tensile flow behaviour of mechanically milled iron and a low-alloy steel are analysed using power law models that describe the evolution of stress–strain during a tensile test. A new analytical power law equation is presented that is shown to be superior to the Hollomon and Ludwigson equation to describe the room temperature flow properties of the low-alloy steel over a wide strain rate range. It not only provides a better fit to the homogenous flow curve of the low-alloy steel but also predicts the maximum strength without the prior knowledge of the uniform strain. The new equation also fitted the flow curves of mechanically milled iron with grain sizes in nano to micrometer range.